Legal analysis of the position of the Attorney General of the Republic of Indonesia not being a political party administrator based on the Constitutional Court of the Republic of Indonesia Decision Number 6/PUU-XXII/2024: General Attourney Position in Indonesia - Karlina, Yunawati; Sapta, Irwan (Jurnal Ilmiah Hukum dan Keadilan, 2025)
This study examines the impact of the Constitutional Court Decision Number 6/PUU-XXII/2024 concerning the Position of the Attorney General of the Republic of Indonesia Not from Political Party Management. This research method is normative legal research with a case study analysis approach. Normative legal analysis. The results of this study are 1. Constitutional Court Decision No. 6/PUU- XXII/2024 Grants the Applicant's request in part. 2. Declare Article 20 of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia (State Gazette of the Republic of Indonesia 2021 Number 298, Supplement to the State Gazette of the Republic of Indonesia Number 6755) is contrary to the 1945 Constitution of the Republic of Indonesia and has no conditional binding legal force as long as it is not interpreted as "To be appointed as Attorney General, one must meet the requirements as referred to in Article 20 letters a to f including the requirement not to be an administrator of a political party unless one has resigned as an administrator of a political party at least 5 (five) years before being appointed as Attorney General". The legal impact of the Constitutional Court Decision of the Republic of Indonesia No. 6/PUU-XXII/2024 on the Attorney General's Office of the Republic of Indonesia is that in order to be appointed as Attorney General of the Republic of Indonesia, one must not be an administrator of a political party at least 5 years before being appointed as Attorney General.